VASEKTOMI DAN PEMOTONGAN TARING MONYET EKOR PANJANG (Macaca fascicularis) DI LOKASI WISATA ULUWATU - I N, Wandia.; Suatha, I K; Soma, I G.; Widyastuti, S. K.; Rompis, A. L. Tenden (Buletin Udayana Mengabdi, 2012)
Population growth and aggressiveness are important factors on macaque populations in which their habitats are used as tourist destinations. Controlling those two factors may decrease the negative impact of population both to its surrounding environment and to the internal circumstance of population. This Community Service was packed as a vasectomy and canine cutting services on the adult male of long tailed macaques occupying a tourist destination of Uluwatu, Badung Regency. Vasectomy is a surgical division of all or part of vas deferens to induce sterility. Surgical resection of part of vas deferens used a bilateral slicing method. Additional medical treatments were also performed according to cases encountered in field. During this performance, one selected adult male was vasectomy-surged and four adult males subjected to canine cutting. An operation of removing rubber encircling the neck of a juvenile macaque was done successfully. Moreover, uprooting snare tied the left leg (near tarsal region) of sub adult male was also performed successfully. A week later, Uluwatu manajement reported that all individuals formerly subjected to medical treatments were in good health and their wounds went to be healing completely.